Optimal stocks for public foodgrain storage in Bangladesh: An assessment of required storage volumes and corresponding investment needs - Dorosh, Paul A. (International Food Policy Research Institute, 2021)
National and household food security in Bangladesh have been greatly enhanced over the past two decades by policies that have allowed a major public foodgrain distribution and relatively large pub-lic stocks to co-exist with private sector trade. Yet, this system has also undergone substantial changes as the structure of the Bangladesh food economy has been transformed in response to growing household incomes, shifts in production and consumption, and changes in international markets.